2002
DOI: 10.1209/epl/i2002-00337-8
|View full text |Cite
|
Sign up to set email alerts
|

Preon trinity—A schematic model of leptons, quarks and heavy vector bosons

Abstract: PACS. 12.15.Ff -Quark and lepton masses and mixing. PACS. 12.60.Rc -Composite models. PACS. 14.60.St -Non-standard-model neutrinos, right-handed neutrinos, etc..Abstract. -Quarks, leptons and heavy vector bosons are suggested to be composed of stable spin-1/2 preons, existing in three flavours, combined according to simple rules. Straightforward consequences of an SU (3) preon-flavour symmetry are the conservation of three lepton numbers, oscillations and decays between some neutrinos, and the mixing of the d … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
(18 reference statements)
1
34
0
Order By: Relevance
“…We have briefly noted their potential importance for dark matter and ultra-high energy cosmic rays, connections that also could be used to observe them. This might provide alternative means for constraining and testing different preon models, in addition to direct tests [8] performed at particle accelerators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have briefly noted their potential importance for dark matter and ultra-high energy cosmic rays, connections that also could be used to observe them. This might provide alternative means for constraining and testing different preon models, in addition to direct tests [8] performed at particle accelerators.…”
Section: Discussionmentioning
confidence: 99%
“…The possibilities are, e.g., supersymmetric particles, new dimensions and compositeness. In this letter we consider "preon models" [7,8], i.e., models in which quarks and leptons, and sometimes some of the gauge bosons, are composite particles built out of more elementary preons. If fermionic preons exist, it seems reasonable that a new type of astrophysical compact object, a preon star, could exist.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the need for observational clues in the cold dark matter sector, this could prove compositeness plausible, without much dedicated effort. This approach might complement direct tests of preon models [13] performed at particle accelerators. …”
Section: Discussionmentioning
confidence: 97%
“…Later, it was shown that with another choice for the gauge group and the flavour structure of preons, e.g., three different preon flavours, the consistency conditions are satisfied [12]. For a more detailed discussion of preon models, see [9,10,13] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…As we have already mentioned, all of the previous composite models explain the observed variety of elementary particles by different combinations of a certain number of preon types, reduced with respect to the number of the fundamental types in the standard model [121][122][123][124][125]. However, it is plain to see that even this reduced number cannot solve the problem.…”
Section: −18mentioning
confidence: 99%